Pengaruh Sosialisasi, Pendidikan Dan Pelayanan Terhadap Tingkat Kesadaran Anggota Dalam Memahami Credit Union Di Cu Tunas Harapan Batam - Balun, Bernardus Somi; Hasugian, Mordong; Sihaloho, Asner (Tractare: Jurnal Ekonomi-Manajemen, 2022)
This research was conducted to find out the influence of socialization, education, service, and awareness level of Credit Union Tunas Harapan Batam members. This study uses a quantitative methodology to investigate correlations. Primary data was obtained by distributing questionnaires to 50 respondents (members) at Credit Union Tunas Harapan Batam and will be tested with validity, reliability test, multiple regression analysis, hypothesis test and determinant coefficient test with SPSS version 22.The results showed that education is not so influential on the level of awareness, while, Socialization and service have a positive and significant impact on the level of awareness in understanding Credit Union Tunas Harapan Batam. The result of determination coefficient test shows that R Square = 0.901 and Adjusted R square = 0.894, it means that awareness level in understanding Credit union of 67,75% can explain that socialization and service have the biggest and significant influence on awareness level (Sig = 0,052)